Understanding Single-Use Plastic (SUP) during the COVID-19 lockdown through digital ethnographic research - Cortes, Erika Marlene; Lara, Pamela Garduño; Mora, David Molina; Ayvar, Ricardo Serrano (My University, 2021)
How do people’s interaction and behaviour change in a world where social contact is suddenly limited? How does ethnographic research change and adapt to new interaction rules? What can we discover through it? During the COVID-19 lockdown, we identified an extensive opportunity for digital ethnography (DE) to explore the evolving social worlds. As the starting point, this research aimed to inquire into the daily use of single-use plastics (SUP) consumption and disposal amongst the community that occupies UNAM’s Posgraduate Unit through the design and application of a set of ethnographic analogic and participative tools. However, the COVID-19 world pandemic detoured our initial research plan and turned it into DE research. This shift required a change of theoretical contents into the comprehension and implementation of DE to rethink the field research. This article registers the adaptation of an ongoing project because of a disruptive event like a pandemic; through it, we want to share our experiences of using DE as a qualitative approach, insights about our project process and our predictive perspective about the growing problem we are facing with SUP.
Keywords: Design Ethnographic Futures; Digital Ethnography; Ethnographic Research; Lockdown; Single-Use Plastics